The sources of value creation in acquisitions of intangible assets - Masulis, Ronald W.; Reza, Syed Walid; Guo, Rong (Journal of Banking & Finance, 2023)
We document that acquirer announcement returns and post-M&A performance rise with a target's proportion of intangible assets. This shareholder wealth creation is associated with profitable acquirers purchasing complementary intangible assets and promising growth options from less profitable targets. Purchase prices are lower when targets face financial constraints limiting their ability to pursue promising investment opportunities. Analyzing acquisitions across different classes of intangible assets and matching successful with failed bids for targets with intangible assets support our main findings and suggest that these results are robust to endogeneity concerns. We conclude that target intangible assets provide important sources of M&A value creation.